Agriculture and environment: Interlink with poverty dimension - Dhakal, Naina (Journal of Agriculture and Environment, 2007)
Despite of development efforts over decades 32 percent of the population is still below poverty line in Nepal. Economic, social, political and environmental factors are thought to be responsible for the poverty. Human effort to derive food for survival has direct and indirect impact on environment. Reducing poverty through income and employment generation is the focus of different development plans. There is interlinking between agricultural farming and environment. To reduce poverty and enhance environment each agricultural project which requires to produce assessment must be assessed economically too. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 74-82